Principles of Executive Functioning Interventions for Children With Cochlear Implants: Guidance From Research Findings and Clinical Experience. Issue 1 (January 2021) - McConkey Robbins, Amy; Kronenberger, William G.
Abstract : N/A: Children with cochlear implants (CIs) are at risk for experiencing deficits in the development of neurocognitive processes known as executive functions (EF). Such deficits likely arise as a consequence of early-onset deafness, the degraded auditory input provided by CIs, and delays in spoken language development. Interventions specifically designed for pediatric CI users are needed to address challenges and delays in EF because of the unique influences of hearing loss and language delay on EF development, which have deleterious, cascading effects on speech and language development and subsequent reading and academic achievement. Because patterns of EF weakness emerge even in the preschool years, interventions to improve EF should be implemented at early ages, while children are young and neuroplasticity is high. Drawing on previous research findings and clinical experience, this paper highlights 10 principles to guide the development of EF interventions for children with CIs. Abstract : Supplemental Digital Content is available in the text